2012
DOI: 10.4161/bact.21440
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high throughput assay for indirectly measuring phage growth using the OmniLogTMsystem

Abstract: The conventional and most accepted method of measuring the lytic activity of a phage against its bacterial host is the plaque assay. This method is laborious, time consuming and expensive, especially in high throughput analyses where multiple phage-bacterial interactions are required to be monitored simultaneously. It can also vary considerably with the experimenter and by the growth and plating conditions. Alternatively, the lytic activity can be measured indirectly by following the decrease in optical densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 18 publications
2
73
0
Order By: Relevance
“…The literature recognizes as evidence of the lytic activity of bacteriophages, reduction in the optical density of host bacteria cocultivated with lytic phages in relation to bacterial cultures without the phage [20]. In our experiments co-cultivating filtered waste water from artisanal poultry processing plants with SE and SI we saw strong evidence of bacteriophages lytic activity by the constant decrease of bacterial concentration comparing with bacterial cultures without the filtrates.…”
Section: Discussionsupporting
confidence: 54%
“…The literature recognizes as evidence of the lytic activity of bacteriophages, reduction in the optical density of host bacteria cocultivated with lytic phages in relation to bacterial cultures without the phage [20]. In our experiments co-cultivating filtered waste water from artisanal poultry processing plants with SE and SI we saw strong evidence of bacteriophages lytic activity by the constant decrease of bacterial concentration comparing with bacterial cultures without the filtrates.…”
Section: Discussionsupporting
confidence: 54%
“…This subset of 98 phages was initially selected for screening because previous work had demonstrated that, collectively, these bacteriophages are highly active against a broad range of MDR A. baumannii isolates (data not shown). Within 18 h of receipt of the first clinical isolate, selection of an appropriate therapeutic cocktail for the original isolate, named TP1, was achieved via an OmniLog-based time-kill assay system (19,20). The bacterial isolates from this study are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, small-scale phage amplifications on their corresponding host bacterium were performed to prepare the A. baumannii-specific phage library, which was subsequently stored at 4°C until required. The growth of A. baumannii clinical isolates TP1, TP2, and TP3 in the presence of phage was evaluated via spot testing and also in a Biolog imaging system (Biolog, Hayward, CA) (19,20). In this case, one covered 96-well plate was used per phage strain and incubated at 37°C for 24 h, with wells positive only for bacteria and test wells with a single phage added at a multiplicity of infection (MOI) of approximately 100.…”
Section: A Baumannii Clinical Isolatesmentioning
confidence: 99%
“…An automated, indirect, liquid lysis assay was used to evaluate the activity of phages against A. baumannii strains (32). Briefly, an overnight culture of each strain was inoculated into the wells of a 96-well plate containing TSB mixed with 1% (vol/vol) tetrazolium dye.…”
Section: Methodsmentioning
confidence: 99%
“…An efficiency-of-plating assay showed that when a dilution series of 10 10 to 10 2 of all four individual phages was spotted on an overlay plate of AB5075P, all four phages could infect at a concentration as low as 10 3 PFU per ml. To demonstrate that phages AB-Navy1-4 were each unique, each was tested against a genetically diverse set of A. baumannii strains to compare host ranges by use of a Biolog system (32). The host range of each phage was distinct, not only when the strains infected were compared but also when the numbers of hours each phage could prevent growth of the bacterial host in liquid (hold time) were compared (Table 1).…”
Section: Characterization Ofmentioning
confidence: 99%